Chronic Treatment with Fluoxetine or Clozapine of Socially Isolated Rats Prevents Subsector-Specific Reduction of Parvalbumin Immunoreactive Cells in the Hippocampus. (10th February 2018) - Filipović, Dragana; Stanisavljević, Andrijana; Jasnić, Nebojša; Bernardi, Rick E.; Inta, Dragos; Perić, Ivana; Gass, Peter
Graphical abstract: Highlights: Chronic social isolation (CSIS) reduced hippocampal parvalbumin-positive (PV+) cells. These changes were prevented by fluoxetine (Flx) or clozapine (Clz). Flx prevented CSIS-induced decrease in the number of PV+ cells in CA2 and CA3 regions. Clz prevented CSIS-induced decrease in the number of PV+ cells in CA2/3 and DG regions. Flx increased the number of PV+ interneurons in CA1 region of control rats. Abstract: The dysfunction of parvalbumin-positive (PV+) interneurons, the most abundant type of hippocampal GABAergic inhibitory interneuron, has been implicated in mood disorders. We recently reported that adult male Wistar rats exposed to three weeks of social isolation show depressive- and anxiety-like behaviors and a reduced number of PV+ interneurons in all hippocampal subregions. As GABA neurotransmission has been proposed as a potential therapeutic target of antidepressant and antipsychotic medications, we examined whether treatment with the antidepressant fluoxetine (Flx) (15 mg/kg/day) or the antipsychotic clozapine (Clz) (20 mg/kg/day) during three weeks of social isolation in rats offered protection from the isolation stress-induced reduction in the number of PV+ interneurons in hippocampal subregions. Using immunofluorescence analysis, we revealed that both chronic Flx and Clz partially prevented the isolation-induced changes. Flx prevented the reduction in the number of PV+ interneurons in the CA2, CA3, without affecting the CA1 and dentate gyrus DG areas, whereas Clz prevented this decrement in the CA2, CA3 and DG regions but not in CA1 areas. Moreover, Flx increased the number of PV+ interneurons in CA1 in control animals. These findings suggest that chronic administration of Flx or Clz may offer partial protection from social isolation stress via modulation of the hippocampal GABAergic system.